Advancing the frontiers of justice to the under represented in Nigeria through public law library legal clinics: issues for consideration. Issue 6 (15th June 2020) - John Bamgbose, Oludayo
Abstract : Purpose: The research sought to explore the role of public law libraries in advancing the net of persons who could access justice, using the law clinic in Nigeria as a gateway. It also examined how public law libraries could fit in drawing justice closer to the people using law clinics. Design/methodology/approach: In achieving the research intentions, the researcher adopted mixed research approach. For the doctrinal method, the study embraced a desktop review of relevant literature on law clinic, access to justice and law libraries. For non-doctrinal method, the researcher brought to bare, his observation, experience and participation in clinical legal education, law clinic and law librarianship for a period of almost a decade. The literature and the experience of the researcher formed the basis on which the paper was developed. Findings: The findings from this research reveal that access to justice is constrained by a number of factors that make it impossible for many Nigerians to access justice. The study further brings to the fore the role of law clinics in widening the gap of access to justice. In addition, the place of public law libraries in expanding the frontiers of access to justice is further underscored. Originality/value: Not minding the potentials of public libraries in advancing access to justice world over, perusal of literature reveals that there is dearth of literature on the role of public law libraries in advancing access to justice through the instrumentality of law clinics in Nigeria. This research appears to be pioneering research in this regard.